CREATIVE AGRICULTURAL TOURISM MANAGEMENT MODEL FOR PRACHARATH BANG BAI MAI FLOATING MARKET, BANG BAI MAI SUB-DISTRICT, MUEANG DISTRICT, SURAT THANI PROVINCE - Kamon RUENGDET; Sangrawee WITOONPAN; Waritsara SOMKEATKUN (Geo Journal of Tourism and Geosites, 2023)
This research aimed to: 1) study concepts and models of creative agricultural tourism management; 2) study factors affecting the behavior of creative agricultural tourism in Pracharath Bang Bai Mai Floating Market; and 3) propose a model for creative agricultural tourism management at Pracharat Bang Bai Mai Floating Market.The data were collected using a questionnaire asking 400 participants. A focus group, observation and interview were used to collect data and descriptive and inferential statistics were used for analysis. 1) The tourism management model is not yet aligned with the needs and behaviors of tourists. The condition of the community area is limited. There are quite a few people who will inherit the knowledge/local wisdom. Most of the activities focus on training rather than learning and exchanging experiences that are delivered to tourists. 2) Factors that affect tourism behavior are: personal factors, economic factors social/cultural factors, technology/innovation factors, public relations factor and tourism infrastructure factors. 3) Tourists are interested in the form of agricultural tourism routes that combine agricultural communities.The results of this research can be used as :1) a guideline for policy formulation to promote tourism and income distribution to the community; 2) a guideline for community resource and tourism management ;3) as a guideline for preserving and inheriting local wisdom from generation to generation; 4) a guideline for creating careers and creating value for the community from creative agritourism, and; 5) a role model for creative agritourism.